If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(-4x + -5) = 99 Reorder the terms: 9(-5 + -4x) = 99 (-5 * 9 + -4x * 9) = 99 (-45 + -36x) = 99 Solving -45 + -36x = 99 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '45' to each side of the equation. -45 + 45 + -36x = 99 + 45 Combine like terms: -45 + 45 = 0 0 + -36x = 99 + 45 -36x = 99 + 45 Combine like terms: 99 + 45 = 144 -36x = 144 Divide each side by '-36'. x = -4 Simplifying x = -4
| 36x+72=180 | | 182=13x+52 | | log(20x-3)-log(x+4)=2 | | 82=2+30+40a | | 0=b^2+b | | 28s-26=40s-2(2s+5) | | 1m+6=7m | | 4x^2-12x=12 | | 1/4(b+2)=10 | | -3x=-2x+3 | | .25y-.6=.15y+3-.8y | | 2xy-7y=49 | | 5+0.02x=4.69+0.08x | | 1400=10x+500 | | 45=-15+5g | | 2(2m-1)+6(m+2)=8m | | 5f+10=6-3f | | 3s-2=1 | | (x-4)=(2x-7) | | -3k-6=-4k-11 | | 5ng-5n+10ng-20n= | | 0.5x+2x=-50 | | -9+p=-11 | | 8k+3-2k=6 | | 9-8m=-8(m-2) | | 44.79=9g+3.84 | | 23x+33=13x+39 | | 3(2t-1)-7=4(t+1) | | 30-5x=50-13x | | 1.48g-9=0.62 | | x(50-2x)(30-2x)=4104 | | -7-9(n+4)=9-7(n+4) |